Improved Cardiovascular Parameter With a Nutrient-Dense, Plant-Rich Diet-Style: A Patient Survey With Illustrative Cases. (May 2017) - Fuhrman, Joel; Singer, Michael
Background . The results presented from a practice survey include cases of interest, demonstrating improvements in cardiometabolic risk factors utilizing a Nutrient-Dense, Plant-Rich (NDPR) diet. It includes changes in weight, blood pressure, and lipids parameters derived from the survey and retrospective chart review. Methods . Practice records and interviews were used for case history descriptions. Participants' data were collected via an online survey. Results . Adherence to a NDPR dietary protocol resulted in reduced low-density lipoprotein cholesterol and serum triglycerides. Compliance of greater than 80% with the target diet resulted in an average sustained weight loss of over 50 pounds in 75 obese subjects. There was a corresponding average reduction of 27.8 mm Hg in systolic blood pressure for the 127 survey responders with untreated hypertension at baseline, and a 42.2 mg/dL average decrease in low-density lipoprotein cholesterol for the 328 survey responders, not on cholesterol reducing medications. Conclusion . The outcomes from both the survey responders and cases demonstrate the potential for the NDPR dietary intervention to improve weight, blood pressure, lipids, and even reverse severe cardiovascular disease. Though this is a report of cases and self-reported benefits, it adds evidence to support the need for further studies investigating the potential of this dietary intervention.